Peningkatan Hasil Belajar Peserta Didik dengan Menggunakan Model Pembelajaran Discovery learning pada Kelas XI MA As’adiyah Putri Sengkang - Rini Hajriani (LPPM Universitas Puangrimaggalatung, 2021)
This research is classroom action research. Teachers who are delivering learning materials do not use varied methods and always use the lecture method, so that most students do not understand and are not active in the learning process which results in unsatisfactory student learning outcomes. The purpose of this study was to determine the increase in student learning outcomes through the Discovery Learning cooperative learning model in biology class XI IPA MA As'adiyah Putri Sengkang. The subjects of this study were students of class XI MA As'adiyah Putri Sengkang, totaling 22 students. It was carried out in two cycles. Each cycle was carried out 3 meetings. At the end of cycles I and II, data was collected using a learning outcome evaluation test. The instruments used in this research are learning outcomes test questions and student activity observation sheets. The results showed that the application of the Discovery Learning learning model could improve student learning outcomes in biology class XI IPA 5 MA As'adiyah Putri Sengkang.